Carotid–femoral pulse wave velocity assessment by two different methods. Issue 9 (September 2015) - Pichler, Gernot; Martinez, Fernando; Vicente, Antonio; Solaz, Elena; Calaforra, Oscar; Redon, Josep
<x xml:space="preserve">Abstract</x> Introduction: Several devices are available for carotid–femoral pulse wave velocity (cfPWV) measurement, and a cut-off value for reference cfPWV has been established. However, discrepancies between devices have been reported. Objectives: The aim of the study was to establish the concordance of two common techniques (Complior and SphygmoCor), taking into account the anatomical distance between the measurement sites, and to investigate the impact on cardiovascular risk stratification. Methods: cfPWV, central and peripheral blood pressure were assessed in patients attending the hypertension outpatient clinic. The subtracted carotid–femoral distance was estimated both according to the manufacturer's recommendations and correcting the obtained values by 10.3%. Bland–Altman plots, Pearson's correlation coefficient, Lin's concordance correlation coefficient and multivariate models were used to investigate the difference in cfPWV. Results: cfPWV assessed in 118 patients (age 55 ± 12 years, 61% hypertensive patients, BMI 28.9 ± 4.4 kg/m2) with the Complior device was lower than that assessed with the SphygmoCor device, regardless of correcting the subtracted carotid–femoral distance (8.7 vs. 10.3 m/s and 9.3 m/s, respectively; P value < 0.001). The average difference was −1.59 ± 1.5 and −0.617 ± 1.39 m/s for corrected and uncorrected SphygmoCor values, respectively, SBP, BMI and female being the main determinants of the difference. Cardiovascular risk stratification changed in up to 40% of the study population, depending on the device and the arterial distance estimation. Conclusion: The concordance between the Complior and the SphygmoCor device is poor when the anatomical artery length is controlled for and in the presence of cardiovascular risk factors, resulting in a difference in classification of cardiovascular risk.